ANALISIS PENERAPAN PSAK 216 PADA PT. WIJAYA KARYA BETON TBK.: PABRIK PRODUK BETON LAMPUNG - Al Amin, Muhammad Ridho; Hendri, Nedi; Alia Fitri, Resti (Jurnal Akuntansi AKTIVA, 2025)
This study aims to analyze the application of fixed asset accounting in non-profit entities with a case study at PT. Wijaya Karya Beton Tbk. (Lampung Concrete Product Factory) and evaluate the suitability of the accounting treatment applied based on PSAK 216. The method used in this study is a qualitative method to understand in depth the application of fixed asset accounting. The data collection technique in this study uses technical triangulation, namely researchers collect data through various methods to obtain information from the same source. The data collection techniques used are interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman model by conducting data collection, data reduction, data display, and drawing/verification. The results of this study The appropriate accounting treatment is recognition, measurement at recognition, measurement after recognition, termination and presentation of fixed assets. The accounting treatment of fixed assets that has not been implemented is disclosure.